The Effect Of Promotion On The Interest Of Visiting Domestic Tourists In Bantimurung Natural Tourist Destination, Maros Regency - Indasari, Indasari; Baharuddin, Aris; Siraj, Muhammad Luthfi; Seppa, Yusi Irensi (Jurnal Administrasi Bisnis, 2025)
This study aims to find out how much influence promotion has on the interest of visiting domestic tourists in Bantimurung Natural Tourism Destinations, Maros Regency. This research uses quantitative research methods. To achieve this goal, researchers use data collection techniques in the form of observations, questionnaires, and documentation. The sample used in this study was 99 tourists. Data obtained from research results that were processed using data analysis and using the SPSS 25 application consisting of validity and reliability tests. Descriptive data analysis techniques. The results showed that the promotion variable (X) consisting of advertising, sales personal, sales promotion, and public relations indicators, and on the visiting interest variable (Y) consisting of indicators of interest, preferences, and information search had a positive and significant influence. This is evidenced from the results of a simple linear regression analysis and a correlation coefficient test of 0.865 which means that the relationship between promotion and visiting interest is in a very strong category. And the coefficient of determination test (R2) was obtained by 0.748 which means that the influence of promotion on visiting interest in the Bantimurung Natural tourist destination of Maros Regency obtained a value of 74.8%, while the remaining 25.2% was influenced by other factors. Keywords: Promotion, Visiting Interest